Die Rolle familiengeschichtlicher Hinweise in der Supervision - Kováts, Eszter Sz. (European Journal of Mental Health, 2009)
The Role of Family History References in Supervision: Supervision aims at grouping and processing experiences obtained in a professional context. It provides the client with a unique, personal method to reflexive experience based learning. Its goals are to strengthen the professional personality, and to change the specific professionalism through learning. Supervision, as a common reflection process, is based on the commitment of the supervised person to learning, and the assumption that the supervised person is able to make specific decisions regarding individual steps. In theory, the supervisor has no right to exceed the professional situations brought under supervision by the given person. However, behind some professional problems, difficulties or conflicts (uncertainties of competence, inhibitions or blocks appearing in certain work situations, conflicts with peers or superiors, etc.) there may lie unprocessed threads, which may be tracked to earlier socialisation experiences or even events or incidents in family history. Originating from personal history or the multi-generation history of a family (e.g. family beliefs, fears, stigmatisation experiences, prohibitions, commands, identity experiences, ‘messages’) these memories often even unconsciously influence the perception and reaction patterns of the supervised, and may lead to the establishment of ‘blind spots’, and thereby the undifferentiated and uncontrolled coalescence of the personal and professional spheres. We may and should especially react to these if they become implicitly expressed during supervision in the shape of metaphors, symbols, stories, etc. However, while doing so one should definitely avoid the danger of exceeding the limits of supervision, and thereby transforming the process into therapy. An individual and a group supervision process serve to illustrate how it is possible to contribute to the increasing of ‘professional self-awareness’ and thereby the strengthening of professional identity by uncovering, increasing awareness of and integrating these personal or family history threads.